Correlative study of diabetic retinopathy in type 2 diabetes mellitus with haemoglobin A1c, duration of diabetes and modifiable risk factors: smoking, alcohol and BMI in adult population attending a tertiary care hospital - Bedi, Nutan; Gulati, Archana O.; Devasthali, Gauri V. (International Journal of Research in Medical Sciences, 2021)
Background: Diabetes is a disease, which if not controlled, affects every cell of the body from head to toe. No wonder it is often referred to as the “SILENT KILLER”. So through our study, we aim to study the correlation between (haemoglobin A1c) HbA1c levels, duration of diabetes and modifiable risk factors with diabetic retinopathy (DR) in patients of type 2 diabetes mellitus. Methods: This study was conducted in 100 patients (200 eyes) who were diagnosed cases of type 2 diabetes mellitus. A detailed history of the duration of diabetes, alcohol intake and smoking and HbA1c levels was taken. Complete ocular examination was done. BMI was also calculated. Results: 2/3rd of the eyes with grade 3 DR were of>10 years duration while 2/3rd of the eyes with grade 2 DR were of 5-10 years duration. Of the eyes with grade 3 DR, all the patients had HbA1c of more than 8. Significant p value shows strong correlation between DR and obesity. No significant correlation of DR was found with alcohol and smoking. Conclusions: The findings in our study endorse the view that duration and HbA1c are important risk factors for occurrence and severity of DR and therefore a regular follow up and good glycemic control is highly essential for the prevention of occurrence and progression of DR. Strong correlation between BMI and DR suggest that lifestyle changes play a pivotal role.